When God and State Don't Dominate: Pragmatism, Political Theology, and Democratic Authority - Farneth, Molly (Political theology, 2019)
Authority is a normative status - not just power but legitimate power. But what distinguishes legitimate and illegitimate power? Combining recent pragmatist work in the philosophy of language with a Hegelian view of power and recognitive relations, I develop a model of authority rooted in non-dominating democratic practices. The result is a pragmatist political theology that is Hegelian in inspiration and radically democratic in practice.